Sosialisasi pelaksanaan Active Case Finding Tuberculosis pada petugas Tuberculosis di Wilayah Kabupaten Sleman - Sri Arini Winarti Rinawati; Nur Hidayat (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
The behavior of Tuberculosis (TB) officers in Yogyakarta in carrying out active case finding activities is still relatively lacking, therefore it is necessary to disseminate active case finding to TB officers. The purpose of this activity is to improve the implementation of TB Active Case Finding (ACF) among TB officers. The method of community service by providing socialization to TB officers in the Sleman area on October 6, 2019. There is an increase in knowledge about activities (ACF), from the results of the 2019 Risbinakes research measurement compared to the measurement results after this outreach (ACF). There was an increase in participants' knowledge about ACF activities, mostly after the socialization was carried out.